Pluralism, poetry, and literacy : a test of reading and interpretive techniques - Kalck, Xavier (New York, NY : Routledge, 2021)
Drawing from Medieval and Renaissance studies, analytic philosophy and pragmatism, Jewish studies, as well as ecocriticism and environmental humanities, this book demonstrates the consistent relationship between pluralism and literacy through the prism of poetry by confronting the history of interpretive practices with examples from American poets Robert Lax, Larry Eigner, Louis Zukofsky, Gary Snyder and Theodore Enslin. Divided into four areas of investigation--the meditative, the analytic, the diasporic and the ecological reader--it is an invitation to turn to premodern reading practices related to spiritual exercises as well as modern reading practices devoted to the critical pursuit of analytical knowledge. This study further reflects on the textual models of Jewish diaspora as another form of dialog between sacred and secular interpretive practices, before examining a final variation on this distinction by looking at the separation between contemplative and investigative perspectives on reading and writing nature.
OCLC-licensed vendor bibliographic record.
Keywords: Criticism; Reading; Poetics; LITERARY CRITICISM / Poetry; LITERARY CRITICISM / General; LANGUAGE ARTS & DISCIPLINES / Literacy